Designer's guide to energy efficient electrical installations. (Institution of Engineering and Technology, 2016)
BS 7671 has always been about capacity, safety and control of electrical installations. Could energy efficiency negate that?A recent harmonised document, IEC 60364-8-1 Low Voltage electrical installations _ Part 8-1: Energy Efficiency, respects the emphasis of safety and operational control in the first instance. It also, however, requires energy efficient electrical installation designs. Using IEC 60364-8-1 as a point of reference, the Designer's Guide to Energy Efficient Electrical Installations:Prepares users for meeting the new challenges and opportunities presented by energy efficiencyExplains the areas likely to be incorporated into BS 7671 and how this will affect electrical installations in the UKKeeps designers ahead of the game when designing future installationsLooks at energy efficiency in a holistic fashion and examines the potential issues caused by just focusing on one or two specific areasExplains the responsibilities of designers and clients in ensuring an energy efficient electrical design.